Importance and relationship between the basic psychological needs and the "reflection" in elite academy soccer players - Chamorro, J. L.; Sanchez Miguel, P. A.; Leo, F. M.; Sanchez Oliva, D.; Amado, D.; Gonzalez Ponce, I.; Pulido, J. J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Self-determination Theory (SDT; Deci Ryan, 1985, 2000; Ryan Deci, 2000) is a motivational theoretical framework, and lies in a continuum of self-determination. The SDT explains three factors that can facilitate self-determined motivation, called basic psychological needs (BPN): autonomy, competence and relatedness with the others. On the other hand, the term `reflection` is included within the theory of self-regulated learning of Zimmerman`s (2006, 2008). Self-regulated learning gives explanation to the progression in learning tasks. Toering (2010) used this model into the soccer field and showed that the variable `reflection` would be in the middle of the self-regulation model of learning for young elite soccer players. The objective of this study was to identify the relationship between motivation, through the satisfaction of BPN, and the learning process, through the variable `reflection`, as well as test the influences regarding a crucial stage for athletes such as transition to the elite sport. Methods: Participants were 478 soccer players, ranging in age from 16 to19 years old (M17.45; SD.71) belonging to the maximum Spanish under-18 division clubs. The instruments used were as follows: autonomy satisfaction by Standage, Duda & Ntoumanis (2005); competence satisfaction from McAuley, Duncan, Tammem, (1989); relatedness satisfaction of Richer & Vallerand (1998) and, for measuring reflection, the scale of `reflection` byPeltier et al. (2006). Results: Firstly, bivariate correlation analysis showed significant positive correlation between `reflection` and the three basic psychological needs (P< .01). Secondly, linear regression analysis revealed that the three basic psychological needs emerged as predictors of reflection. . The model has a R.433, R2.182 and significance level under .001. The three basic psychological needs significantly predict the `reflection` under .01 and ß09 for autonomy, ß. 161 for the competence and ß.191 for the relatedness. Discussion: This study showed how in the field of sport and, and particularly in soccer, motivation, through the BPN satisfaction (Ryan Deci, 2000), and self-regulation learning, through the `reflection` (Toering 2010) were not only related to each other, but it is important to note that working the BPN in soccer, we can influence the learning process of the different variables that influences on sport performance, aspects crucial for the development and adaptation into elite sport.